Haloarchaeal gas vesicle nanoparticles displaying Salmonella antigens as a novel approach to vaccine development - DasSarma, P. (Procedia Vaccinol, 2015)
A safe, effective, and inexpensive vaccine against typhoid and other Salmonella diseases is urgently needed. In order to address this need, we are developing a novel vaccine platform employing buoyant, self-adjuvanting gas vesicle nanoparticles (GVNPs) from the halophilic archaeon Halobacterium sp. NRC-1, bioengineered to display highly conserved Salmonella enterica antigens. As the initial antigen for testing, we selected SopB, a secreted inosine phosphate effector protein injected by pathogenic S. enterica bacteria during infection into the host cells. Two highly conserved sopB gene segments near the 3′-region, named sopB4 and sopB5, were each fused to the gvpC gene, and resulting SopB-GVNPs were purified by centrifugally accelerated flotation. Display of SopB4 and SopB5 antigenic epitopes on GVNPs was established by Western blotting analysis using antisera raised against short synthetic peptides of SopB. Immunostimulatory activities of the SopB4 and B5 nanoparticles were tested by intraperitoneal administration of SopB-GVNPs to BALB/c mice which had been immunized with S. enterica serovar Typhimurium 14028 ΔpmrG-HM-D (DV-STM-07), a live attenuated vaccine strain. Proinflammatory cytokines IFN-γ, IL-2, and IL-9 were significantly induced in mice boosted with SopB5-GVNPs, consistent with a robust Th1 response. After challenge with virulent S. enterica serovar Typhimurium 14028, bacterial burden was found to be diminished in spleen of mice boosted with SopB4-GVNPs and absent or significantly diminished in liver, mesenteric lymph node, and spleen of mice boosted with SopB5-GVNPs, indicating that the C-terminal portions of SopB displayed on GVNPs elicit a protective response to Salmonella infection in mice. SopB antigen-GVNPs were also found to be stable at elevated temperatures for extended periods without refrigeration. The results show that bioengineered GVNPs are likely to represent a valuable platform for antigen delivery and development of improved vaccines against Salmonella and other diseases.